Seventy years of contribution to Gynecologic Oncology - Galdos Kajatt, Oscar (2017)
The Peruvian Society of Obstetrics and Gynecology has contributed to the development of Gynecologic Oncology in the Peruvian medical community, through papers in The Peruvian Journal of Gynecology and Obstetrics, annual meetings, symposia, precongress courses, courses for residents and other academic activities. The most developed topic in the journal has been cervical cancer, which is the main problem in our country, followed by ovarian and breast cancer.